A matter of behavioral cost: Contextual factors and behavioral interventions interactively influence pro-environmental charging decisions. (December 2022) - Kramer, Jule; Petzoldt, Tibor
Abstract: The sale of electric vehicles (EVs) is steadily increasing, leading to a huge demand of electricity, which needs to be produced CO2 -neutral to make EVs a green alternative. To address this issue, smart charging shifts the charging process to optimal day/night times when (green) energy is available and electricity consumption is low. Especially when charging in public, smart charging may produce external behavioral costs (e.g., charging delays) that should be offset by individual and highlighted environmental benefits. We examined the interactive influence of contextual factors (i.e., charging delay, walking distance, price saving) and behavioral interventions (i.e., framing, social norm, gamification) on green smart charging decisions in an online experiment ( N  = 286). The results showed that the interventions influenced the decision to choose the smart charging station over a convenient non-sustainable alternative when behavioral costs were small to moderate. In situations with no or only negligible extra costs, participants did not need additional persuasion, whereas in high-cost situations, behavioral interventions were insufficient to influence behavior. Highlights: Behavioral strategies promoted green charging choices when costs were moderate. In situations with no/negligible extra costs, interventions were not needed. When behavioral costs were too high, interventions were not sufficient.